Vulgar Expressions among Youth in Duma Village (A Sociolinguistic Perspective) - Sartika Samad; Agus Boriri (Jurnal Langua, 2020)
This research was conducted with the aim of 1) Describing the form of vulgar language used by adolescents in Duma Village, West Galela District. 2) Knowing the context of the use of vulgar language which is often used by adolescents in Duma Village, West Galela District. This research uses descriptive qualitative research methods. Through this qualitative descriptive method, the researcher will describe the use of swear language by adolescents in Duma Village, West Galela District. The place of research used by researchers for research (observation) is in Duma Village, West Galela District. Researchers conducted research in Duma Village with the consideration that researchers are part of the Duma community so that it will facilitate researchers in the data collection process. The time needed in this research is 2 (two) months, starting from May to July 2020. Data collection techniques are observation, interviews, and documentation. To perform data analysis, researchers used qualitative techniques, namely data reduction, data presentation, and conclusion drawing. The results of the study prove that 1) the form of vulgar language (swearing) used by adolescents in Duma Village, West Galela Subdistrict, there are two forms, namely cursing which is used based on the form of word units used by Duma adolescents in smaller word units and cannot be broken down again. In addition, there are curses used by teenagers in the form of phrases in the form of units that do not exceed the limits of the elements of the grammatical function. 2) The context of using vulgar language (swearing) which is often used by adolescents in Duma Village, West Galela Subdistrict, is a form of emotional outburst when angry, teasing friends, joking, admiring, and insulting fellow teenagers. The context of the use of cursing by teenagers in Duma is both conscious (intentional) and unconscious (unintentional).